Systems of Judicial Review of Administration - Radošević, Ratko (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
Systems of judicial review of administration are the result of the differences between Common Law and Civil Law countries, as well as the specific historical circumstances that have led to a different understanding of the principles of separation of powers and thus the relation between administration and courts. The aim of this paper is to point out the traditional differences between the systems of judicial control of administration and the contemporary tendencies in their development. In the contemporary sense, there is a transformation of the basic features of these systems that were previously determined as important. Today, they are not so clearly and strictly separated and it is harder to use them as the criteria of the separation.